Maskless patterned growth of ZnO nanorod arrays using tip based electrolithography. (April 2018) - Kathalingam, A.; Vikraman, Dhanasekaran; Karuppasamy, K.; Kim, Hyun-Seok; Park, Hyun-Chang; Shanmugam, Kumaran
Abstract: We report patterned growth of ZnO nanorods based on electrochemical driven writing on a PMMA layer using a metal tip. Electric field induced breaking of the PMMA layer was used for pattern formation. ZnO nanorods were grown on the patterned PMMA layer using two step hydrothermal synthesis. After etching the unaffected PMMA using the conventional lift-off process, patterned growth of vertically aligned ZnO nanorods was produced. This strategy provides an easy and innovative solution for submicron lithographic patterning without requiring complex mask alignment, and allows micro-level semiconductor patterns to be easily formed. The process of pattern formation and ZnO nanorods growth are reported.